2022
DOI: 10.1124/molpharm.122.000590
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Sustained Cellular Effects of MET inhibitors Are Driven by Prolonged Target Engagement and Lysosomal Retention

Abstract: Intracellular distribution of drug compounds is dependent on physicochemical characteristics and may have a significant bearing on the extent of target occupancy and, ultimately, drug efficacy. We assessed differences in the physicochemical profiles of MET inhibitors capmatinib, crizotinib, savolitinib, and tepotinib and their effects on cell viability and MET phosphorylation under steady-state and washout conditions (to mimic an open organic system) in a human lung cancer cell line. To examine the differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In contrast, capmatinib was applied only after pembrolizumab treatment, a 25% dose reduction, and an increased dose of dexamethasone may have avoided serious TRAEs. Recent studies have reported alterations in metabolic pathways induced by CYP3A ( 9 ) and the ability of capmatinib and tepotinib to access lysosomes ( 10 ), but none of these features for the MET-inhibitory investigational drug; these differences may also have influenced TRAEs. In addition, the tumor progressed after the first-line MET inhibitor treatment but responded to capmatinib.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, capmatinib was applied only after pembrolizumab treatment, a 25% dose reduction, and an increased dose of dexamethasone may have avoided serious TRAEs. Recent studies have reported alterations in metabolic pathways induced by CYP3A ( 9 ) and the ability of capmatinib and tepotinib to access lysosomes ( 10 ), but none of these features for the MET-inhibitory investigational drug; these differences may also have influenced TRAEs. In addition, the tumor progressed after the first-line MET inhibitor treatment but responded to capmatinib.…”
Section: Discussionmentioning
confidence: 99%
“…The 45-minute incubation with tepotinib was sufficient to completely inhibit HGF-induced MET phosphorylation 14 hours after withdrawal of tepotinib, with an IC 50 value of 5.3 nmol/L ( 30, 33 ), demonstrating rapid uptake and cellular retention of tepotinib, with long-lasting MET inhibition. Persistence of tepotinib inhibition under washout conditions may be explained by the long residence time of tepotinib and its retention in the lysosomal compartment to provide a local drug reservoir ( 41 ). Furthermore, 10% (v/v) serum only moderately affected tepotinib inhibition of HGF-induced MET phosphorylation in A549 cells (average IC 50 values of 21 and 23 nmol/L with murine and human serum, respectively; ref.…”
Section: In Vitro Pharmacology Of Tepotinibmentioning
confidence: 99%